Experimental realization of two-dimensional Dirac nodal line fermions in monolayer Cu2Si - Baojie Feng; Botao Fu; Shusuke Kasamatsu; Suguru Ito; Peng Cheng; Cheng-Cheng Liu; Ya Feng; Shilong Wu; Sanjoy K. Mahatha; Polina Sheverdyaeva; Paolo Moras; Masashi Arita; et al. (Nature Communications, 2017)
Nodal line semimetals have been observed in three-dimensional materials but are missing in two-dimensional counterparts. Here, Feng et al. report two-dimensional Dirac nodal line fermions protected by mirror reflection symmetry in monolayer Cu2Si.